PERANCANGAN SISTEM INFORMASI KAS BERBASIS WEB DENGAN MENGGUNAKAN METODE WATERFALL - Fitri Wahyuni (Universitas Methodist Indonesia, 2023)
The Cirebon City Youth and Sports Service (Dispora) is an autonomous implementing element in the field of sports. This field has a section that manages data on government and non-government activities in Cirebon City. One of them relates to information related to sports in the city of Cirebon. As part of the Cirebon City Youth and Sports Service, they do not yet have an adequate or dynamic financial reporting web, so this agency must develop a dynamic web-based information system to accommodate cash management. System development follows the Waterfall concept, which includes the stages of analysis, design, coding, implementation and maintenance. Data collection procedures were carried out through observation, interviews and documentation studies. The design of this website provides convenience in submitting financial reports to agencies.